European guidelines for the qualification of Healthcare Clown Professionals according to the European Credit System for Vocational Education and Training (ECVET) system and the European Qualifications Framework (EQF) - Olshansky, Y; Arriaga, P.; Simonds, C.; Salimbeni, O.; Lie, V.; Kalivoda, R.; Mallard, C.; Stang, F.; Milovska, M.; Costa Fernandes, S. (2019)
This report is the first output developed within the Health Care Clown Pathways (HCCP) Erasmus+ project and presents the European guidelines for the qualification of Healthcare Clown professionals. It outlines the rationale for recognising Healthcare Clowning as a formal professional field, reviews its role and benefits in healthcare settings, and defines the key learning outcomes required for professional qualification in terms of knowledge, skills, and competences. The guidelines were informed by two surveys conducted with healthcare clowns from different European countries: one focused on the qualifications, training requirements, eligibility criteria, learning goals, activity sectors, and assessment methods considered important for professional preparation, while the second examined the impact of the COVID-19 pandemic on healthcare clowns’ work. The report is also complemented by appendices including the survey instruments and results, an overview of healthcare clown organisations in Europe, and examples of existing training programmes. The guidelines are aligned with the European Qualifications Framework (EQF) and the European Credit System for Vocational Education and Training (ECVET) to support a common, transferable, and recognisable professional pathway across Europe. The report was written in English and also adapted and translated into Portuguese, French, Italian, Latvian, and Norwegian.